Days alive and out of hospital after laparoscopic cholecystectomy. Issue 11 (17th October 2022) - Alexander, Harry; Moore, Matthew; Hannam, Jacqueline; Poole, Garth; Bartlett, Adam; Merry, Alan
Abstract: Background: Days alive and out of hospital (DAOH) is a metric that incorporates several outcomes into a single, standardized measure. This study aimed to explore the utility of DAOH in assessing the outcomes of a retrospective cohort of patients undergoing laparoscopic cholecystectomy (LC). Methods: Patients undergoing LC at Auckland City Hospital between 1 January 2010 and 31 August 2015 were included. DAOH values were calculated for the 90 days from the date of surgery (DAOH90 ) and described using median and interquartile ranges (IQR). DAOH90 distributions were compared using a two‐tailed (non‐parametric) Wilcoxon‐Mann–Whitney test. Results: 1652 patients undergoing LC were studied. Patients experiencing complications ( n  = 70, 4.2%) had fewer DAOH90 (median 83, IQR 79, 86) than patients who underwent uncomplicated LC (median 88, IQR 86, 88), P  < 0.001. Patients who were converted to open cholecystectomy ( n  = 70, 4.2%) also had fewer DAOH90 (median 82.5, IQR 79, 84) than patients who underwent uncomplicated LC, P  < 0.001. Post‐operative complications and conversion had a statistically significant effect on DAOH90 at each of the tested quantiles, except for conversion at the 0.1 quantile. Conclusion: DAOH90 is readily calculable from existing New Zealand administrative data sources and is sensitive to the occurrence of complications after LC. Abstract : Days Alive and Out of Hospital (DAOH) is a novel composite outcome measure. This Study applied DAOH to a retrospective cohort of laparoscopic cholecystectomy (LC) patients. DAOH is readily calculable from existing New Zealand databases and is sensitive to the occurrence of complications after LC.